The effect of temperature and pressure on polycaprolactone morphology. (16th March 2020) - Baptista, Cameron; Azagury, Aharon; Shin, Hyeseon; Baker, Christopher M.; Ly, Eileen; Lee, Rachel; Mathiowitz, Edith
Abstract: The morphology and melting behavior of poly(ε-caprolactone) (PCL) processed at varying pressure-temperature-time conditions (2000–20, 000 lbf, 22–70 °C, and 5–15 min) were studied using polarized light microscopy (PLM), differential scanning calorimetry (DSC), and X-Ray diffraction (XRD). Samples processed well below the melting region at 22 °C displayed minimal to no birefringent properties, with broadened crystalline XRD scattering patterns, indicative of plastic crystal mesophase morphology. Plastic crystal quantity was shown to gradually increase from 16% to 30% with processing pressure increasing from 2000 lbf to 20, 000 lbf . The mechanism of this formation is thought to be the result of crystal disorganization upon plastic deformation, related to the low-energy barrier slip-planes in the crystalline structure. With sufficient chain mobility achieved at higher processing temperatures (50 °C and 60 °C), samples displayed broad birefringent strokes under PLM and were characterized by XRD scattering patterns of broad anisotropic arcs around the equator of the 2D azimuthal pattern, which are indicative of condis crystal mesophase orientation. As opposed to plastic crystal, the condis crystal quantities showed no correlation with increased pressure, ranging between 28% and 40% as processing pressure increased. The additional chain mobility at these temperatures is thought to enable the mesophase to orient radially (normal to the direction of the external load), allowing the transition from plastic crystal to condis crystal. Thus, this paper reports the formation of four distinct morphologies upon processing PCL namely; crystalline, condis crystal mesophase, plastic crystal mesophase, and amorphous. Graphical abstract: Image 1 Highlights: The morphology and melting behavior of PCL was analyzed after processed at varying pressure-temperature-time conditions. Samples processed at 22 °C displayed morphology indicative of plastic crystal mesophases. Samples processed at 50 °C and 60 °C displayed morphology indicative of condis crystal mesophases. Samples processed at 70 °C (above T m ) displayed typical semi-crystalline morphology. Plastic crystal quantity was shown to increase with increasing processing pressure. Condis crystal quantities showed no correlation with increased pressure.